Public health emergencies of international concern: a historic overview - Wilder-Smith, Annelies; Osman, Sarah (Journal of travel medicine, 2020)
The International Health Regulations (IHR) have been the governing framework for global health security since 2007. Declaring public health emergencies of international concern (PHEIC) is a cornerstone of the IHR. Here we review how PHEIC are formally declared, the diseases for which such declarations have been made from 2007 to 2020 and justifications for such declarations.Six events were declared PHEIC between 2007 and 2020: the 2009 H1N1 influenza pandemic, Ebola (West African outbreak 2013-2015, outbreak in Democratic Republic of Congo 2018-2020), poliomyelitis (2014 to present), Zika (2016) and COVID-19 (2020 to present). Poliomyelitis is the longest PHEIC. Zika was the first PHEIC for an arboviral disease. For several other emerging diseases a PHEIC was not declared despite the fact that the public health impact of the event was considered serious and associated with potential for international spread.The binary nature of a PHEIC declaration is often not helpful for events where a tiered or graded approach is needed. The strength of PHEIC declarations is the ability to rapidly mobilize international coordination, streamline funding and accelerate the advancement of the development of vaccines, therapeutics and diagnostics under emergency use authorization. The ultimate purpose of such declaration is to catalyse timely evidence-based action, to limit the public health and societal impacts of emerging and re-emerging disease risks while preventing unwarranted travel and trade restrictions.